A waste heat utilization system for carbonic acid tombarthite is dried - WANG ZHONGQING; WANG DAHAI; CHEN ZHONG; MAO ZHILUN (2018)
The utility model belongs to the technical field of waste heat utilization, concretely relates to a waste heat utilization system for carbonic acid tombarthite is dried, mainly involve and calcine cellar for storing things, pneumatic drying pipe, whirl desicator, cyclone collector, pulse bag dust collector ware, draught fan, heat exchanger and connect in order, the free water and the water of crystallization that contain the carbonic acid tombarthite part to deviate from for the temperature that gets into the pulse bag dust collector ware reduces, effectual protection filter bag, thus increased surplus utilization of heat. 本实用新型属于余热利用技术领域，具体涉及种用于碳酸稀土烘干的余热利用系统；主要涉及到煅烧窖、气流干燥管、旋流干燥器、旋风收集器、脉冲布袋除尘器、引风机、换热器顺次连接；将碳酸稀土含有的自由水和结晶水分开脱出，使得进入脉冲布袋除尘器的温度降低，有效的保护滤袋，从而增加了余热的利用。